Nutrient Profiling Model Towards Recommendation of A Healthy Diet: A Scoping Review - Ruhaya Salleh; Roslee Rajikan; Suzana Shahar; Mohd Razif Shahril; Siti Masitah Elias; Noor Ani Ahmad (Food and Nutrition Society of Indonesia (PERGIZI PANGAN Indonesia) and Department of Community Nutrition, 2024)
Vol. 18 No. 3